PTU-325 Developing a pelvic radiation disease service – which patients do we see in a regional secondary care centre?. (22nd June 2015) - Stacey, R; Cox, B; Turner, J; Green, J
Abstract : Introduction: Pelvic radiation disease (PRD) is a common yet under recognised condition causing significant gastrointestinal symtptoms in patients who have recieved radiotherapy for pelvic malignancy. Most studies to date have involved large, sub specialist centres, but the situation in other regions of the UK is unclear. Recent studies have advocated an algorithm based approach to managing these patients. 1 We have set up a PRD service as part of our general gastroenterology clinic and direct access endoscopy services. We performed a service evaluation to identify the trends of patients presenting to our service, and the investigations that we were performing. Method: Using a database search and retrospective notes analysis, we identified patients seen by the gastroenterology service between 2005 and 2014 with PRD. We noted their initial cancer diagnosis, symptoms and investigation results. Results: 108 patients were identified (57 female, 51 male). Overall median age was 70 years, however women were younger (median age 67 years) than men (76 years). The majority of male patients had urological malignancy (84%), in contrast to gynaecological (64%) in the female group. All males with urological malignancies were treated for prostate cancer. Rectal bleeding (43%) and diarrhoea (42%) were the most common symptoms recorded. Other symptom frequencies are outlined in Table 1 . 88% of patients (n = 84) had more than one symptom at presentation. For patients experiencing rectal bleeding, endoscopy revealed angioectasia and radiation proctopathy in 49%, whereas Bile acid diarrhoea was the most common diagnosis made in the diarrhoea group, with 40% of SeHCAT scans being abnormal. Other diagnositic yields of performed tests included positive results in 20% of glucose hydrogen breath tests, 33% of lactose breath tests and 36% of positive fructose breath tests respectively. Conclusion: Patients with PRD present with a variety of multiple symptoms following radiotherapy for pelvic malignancy. Service development to cater for this group must include adequate access to investigations and endoscopy. Although patients often require large numbers of investigations, the diagnostic yields are high. Disclosure of interest: None Declared. Reference: Andreyev HJN, Benton BE, Lalji A, et al . Algorithm-based management of patients with gastrointestinal symptoms in patients after pelvic radiation treatment (ORBIT): a randomised controlled trial. Lancet 2013;382(9910):2084–2092